2009
DOI: 10.4081/or.2009.e26
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of ligament balancing in total knee arthroplasty: how important is it? A systematic review of the literature

Abstract: Ligament balancing affects many of the postoperative criteria for a successful knee replacement. A balanced knee contributes to improved alignment and stability. Ligament balancing helps reduce wear and loosening of the joint. A patient with a balanced knee is more likely to have increased range of motion and proprioception, and decreased pain. All these factors help minimize the need for revision surgery. Complications associated with ligament balancing can include instability caused by over-balancing and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 99 publications
0
56
0
2
Order By: Relevance
“…Of the ligaments considered, lateral compartment loading was most sensitive to the ITB. Given the clinical significance of soft tissue balancing and known effects on long-term TKR function and longevity [66], our modeling framework may aid surgeons in positioning components and in planning soft tissue releases.…”
Section: Discussionmentioning
confidence: 99%
“…Of the ligaments considered, lateral compartment loading was most sensitive to the ITB. Given the clinical significance of soft tissue balancing and known effects on long-term TKR function and longevity [66], our modeling framework may aid surgeons in positioning components and in planning soft tissue releases.…”
Section: Discussionmentioning
confidence: 99%
“…20 Ligamentous alignment and component attenuation are intrinsically linked. 13 Imbalance may manifest as stiffness, instability, prosthetic loosening, tibiofemoral incongruency, or as defects in patellofemoral tracking. 13,21 In a study by Babazadeh et al, 86% of knees with asymmetrical component wear lacked ligamentous balance.…”
Section: Etiology Of Tka Failurementioning
confidence: 99%
“…13 Imbalance may manifest as stiffness, instability, prosthetic loosening, tibiofemoral incongruency, or as defects in patellofemoral tracking. 13,21 In a study by Babazadeh et al, 86% of knees with asymmetrical component wear lacked ligamentous balance. This study also found that balanced knees have a significantly lower rate of prosthetic loosening.…”
Section: Etiology Of Tka Failurementioning
confidence: 99%
See 2 more Smart Citations